Funcionalidad familiar e ideación suicida en los adolescentes del colegio de bachillerato particular Miguel Ángel Suárez de la ciudad de Loja - Paccha Castillo, Mercy Pamela (2022)
The role of the family is fundamental, since the lack of harmonious family relations can lead to problems of adaptation or behavior, increasing their vulnerability to this problem. Suicidal ideation involves negative ideas or thoughts of wanting to die, which may or may not have antecedent of planning to carry it out. It is important to treat these types of thoughts early to avoid life-threatening consequences. Nowadays, it is more common to have this type of thoughts in adolescents, because of the changes that are distinctive of their age. The purpose of this research work was to analyze the relationship between the levels of family functionality and suicidal ideation in adolescents of the "Miguel Ángel Suárez" Private Baccalaurate High School by means of a quantitative, non-experimental, descriptive and correlative study in a sample of 53 adolescents aged 15 to 19. Data were collected through the Family Functioning Questionnaire (FF-SIL) and the Beck Suicide Ideation Scale (SSI). A higher percentage prevailed in moderately functional families and a higher low risk of suicidal ideation. According to Tu-c Kendall cross table, it was evident that in this population there is no correlation between levels of family functionality and suicidal ideation. As a result, an intervention plan focused on adolescent biopsychosocial well-being and family harmony was developed